The Impossibility of Criminal Justice Ethics: Toward a Phenomenology of the Possible - Polizzi, David (International journal of offender therapy and comparative criminology, 2019)
Regardless the specific theoretical perspective, all ethical formulations for criminal justice practice in some way construct the ontological character of the offender, which, in turn, situates both epistemology and method. How this ethical process ultimately constructs the offender will likely help to establish the degree of ethical worth such an individual is deemed worthy to receive. Whether based upon the seriousness of the crime or based upon the specific configuration of the architecture of incarceration, the very possibility of legitimate ethical practice is greatly compromised. Such results can be better avoided when the ethical import of the individual is ontologically situated within the very definition of what it means to be human. By situating this discussion within the context of the analytic psychology of Carl Jung and his concept of the shadow and the originary ethics of Martin Heidegger found in Being and Time, a more ontologically configured possibility for a criminal justice ethics can be recognized.